Effects of Simulation-Based Learning and One Way to Analyze Them. Issue 4 (1st October 2020) - Lohmann, Robert
Abstract: This contribution presents and discusses the methodology and results of a panel study analyzing the effects of a simulation on students' learning outcomes. The focus is on how sustainable knowledge acquisition can be enhanced through participation in simulation as well as on presenting and discussing one way this learning can be analyzed. The subject of the analysis is a panel survey of students from a German university of applied science. The students have been confronted with a combination of test and self-assessment questions in several waves. The specifications are that the study is designed as a panel survey (pretesting and several posttests) as well as that the knowledge acquisition through the simulation is compared to traditional teaching methods, in this case a lecture. Initial results show that the participants' level of learning success is highest, especially in the part of the simulation in which the participants are active in a kind of role-playing game themselves.